"Being a Careful Observer": The Design of Work‐Related Assignments in Higher Education. Issue 163 (3rd September 2019) - Frison, Daniela; Tino, Concetta
Abstract: This chapter focuses on work‐related learning in higher education and the key principles to consider for the design of work‐related assignments in partnership with business.